KEMAMPUAN MEMBACA PEMAHAMAN MELALUI MEDIA KASET REKAMAN PADA ANAK TUNANETRA - Awaliyah, Hani (Pendidikan Luar Biasa, 2012)
Abstract; The aims of this research are to analyze the application of cassete recording media to reading comprehension, describe the increase of reading ability through cassette recording media,and to minimize students “mistakes in reading comprehension. This is a classrrom action research  which uses Kemmis and Taggart model with 4 stages i.e. planning, action,observation and test.  The data collecting techniques are interview, observation and test.The data analysis was carried out descriptively through reflections of the cycles. The research was conducted in 2 cycles in five meetings . Cycle I consisted of thre meetings with mean = 64%,and it indicates that the students have not achieved mastery learning (75 % ). In the next cycle that is cycle II which consisted of 2 meetings, the mean = 76 % ,which indicates that there is 12 % increase and it shows that the students have achieved mastery learning. Based on the finding of the research,it is concluded that “the reading comprehension ability of the blind students increases if cassette recording media is used in the teaching and learning process “.